The Optimal Consumption of Depletable Natural Resources - Weinstein, Milton C.; Zeckhauser, Richard J. (Quarterly Journal of Economics, 1975)
I. Introduction, 371. — II. The simple model, 372. — III. Market equilibrium in the simple model, 375. — IV. The extended model — optimal and equilibrium allocation with nonzero extraction costs, 377. — V. Equilibrium with uncertain future demand, 381. — VI. Monopoly behavior, 387. — VII. Summary and conclusion, 389. — Appendix: proof of the optimality of the N-period market equilibrium under uncertainty if suppliers are risk-neutral, 390.